A Density Functional Theory study of molecular hydrogen adsorption on Mg site in OFF type zeolite cluster - Yüksel, Numan; Köse, Ahmet; Fellah, Mehmet Ferdi (Pergamon-Elsevier Science Ltd, 2020)
In this study, hydrogen molecule adsorption was investigated on additional framework of Mg atom in OFF type zeolite by way of DFT (Density Functional Theory). The adsorption enthalpy and adsorption energy, chemical potential, HOMO energy, electronegativity, LUMO energy, chemical hardness values have been computed on a 8T zeolite cluster model and compared with those of Mg exchanged ERI, LTL and DFT zeolite structures previously reported in literature. Hydrogen adsorption enthalpy value was computed as -17 kJ/mol. This value is meaningfully larger than the hydrogen molecule's liquefaction enthalpy value. This accordingly specifies that Mg-OFF zeolite structure appears to be an encouraging candidate cryoadsorbent for hydrogen storing. (c) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
FELLAH, Mehmet Ferdi/0000-0001-6314-3365
Keywords: Hydrogen adsorption; DFT; Mg atom; OFF zeolite; Offretite